Effect of zein-based microencapsules on the release and oxidation of loaded limonene. (November 2018) - Chen, Yu; Shu, Meng; Yao, Xiaoxue; Wu, Kao; Zhang, Kun; He, Yating; Nishinari, Katsuyoshi; Phillips, Glyn O.; Yao, Xiaolin; Jiang, Fatang
Abstract: Limonene is a kind of widely used flavor oil, susceptible to degradation with the loss of lemon-like odors and the formation of off-flavors. This study aimed to develop a novel structurally well defined zein-based core-shell microencapsules loaded with limonene for limonene protection and controllable release. The microencapsules were fabricated using a two-step heterogeneous precipitation process, with the shell being formed by direct zein precipitation on the oil-water interface and growing along with the water addition driven by hydrophobic interaction. The formation of core-shell microencapsules occurred at the limonene/zein ratio around 2.0 with D4, 3 close to 10 μm and shell thickness about 25 nm, while the smaller self-assembled zein particles could be formed at the ratio of 0.1 and 5.0, suggesting that the mass ratio of core to shell affected the formation of encapsulation and the shell thickness could be controlled. An interior rough and porous shell of the microencapsules was also observed. Sodium caseinate (SC) was adsorbed onto hydrophobic zein surface by electrostatic interaction, contributing to a hydrophilic interface and improving the re-dispersibility of the freeze-dried powder in water. The release rate of limonene in the burst release phase from zein-SC microencapsules was significantly lower than that of whey protein isolate (WPI)-stabilized emulsion, and tended to be gradual in the sustained phase, followed the zero order kinetics. The limonene retention rate of the microencapsules was higher than that of the WPI-stabilized emulsion during an acceleration storage condition, attributing to the solid barrier of the zein-SC shell of the microencapsules. High linear relationship (R 2 > 0.96) between limonene retention rate and storage time in both microencapsules and WPI-stabilized emulsion was observed, suggesting potential controllability of limonene degradation. The ability to design the natural biopolymer-based colloidal microcapsules with slow-release and oxidation prevention of the unstable flavor oils opens a new opportunity in a stable dispersions in aqueous foods. Graphical abstract: The core-shell structure of the limonene microencapsules was confirmed with CLSM (A) and SEM (B), which was prepared with 4 wt% limonene, 2 wt% zein and 1 wt% SC. The interior rough and porous shell was promising for the rate-limiting release of the core limonene. Image Highlights: A novel zein-sodium caseinate bilayered shell-core microencapsules was fabricated. Zein was precipitated on the oil-water interface driven by hydrophobic interaction. Sodium caseinate was used to improve the re-dispersibility of powder. The release and oxidation of limonene in microencapsules was significantly delayed.